Import demand function for Turkey - Olcay Yucel Culha; Okan Eren; Ferya Ogunc (Central Bank Review (CBR), 2019)
This study revisits the import demand function for Turkey using the newly defined national income data and examines the evolution of the income and price elasticities over time. In this respect, demand functions are estimated for the total imports and its subcomponents separately, and the corresponding time varying elasticities are obtained by applying the method of Kalman filter between 2003 and 2018. The findings suggest that the growth of total imports is mainly explained by income and relative price changes. The income and expenditure elasticities decrease over time in total imports and in sub-components except for intermediate goods. The relative price elasticity remains almost unchanged for investment and consumption goods imports but increases considerably for the intermediate goods imports and total imports.
Keywords: C13; C51; F17; 330; Import demand; Income elasticity; Relative price elasticity; Kalman filter; Turkish economy